Sports Education in Senior High Schools: Analysis of Educational Technology Learning (ETL) During Covid-19 - Ade Rahmat; Iskandar Iskandar (Inspiree)
The  purpose  of  the study. to analyze the factors that affect the learning outcomes of Physical Education, Sports, and Health of class XI students at Senior High School. there are three factors that can affect the learning outcomes of Physical Education, Sports and Health, namely factors contained within students (internal factors), factors that come from outside (external factors) and factors from the learning approach of the students themselves.